Black People’s Unemployment and Urban Violence in John E. Wideman’s Narratives - AZON, Sènakpon Adelphe Fortuné (My University, 2020)
Abstract This article offers a reading of the fiction of the AfricanAmerican novelist John Edgar Wideman that goes against the grain of the popular cliché of the propensity among Blacks in the United States to laziness, and therefore to work refusal, and to the violence that is consubstantial to large urban pockets hit by mass unemployment. It draws its examples from a corpus made up of the Homewood Trilogy, A Glance Away, Philadelphia Fire, and Reuben, around which it articulates its reflection, demonstrating that African Americans are victims of a historical and social context of discrimination against which they must, however, fight for their development. The Marxist literary approach and the Critical Race Theory have been used as the theoretical framework for the study. Résumé Le présent article offre de la fiction du romancier AfroAméricain John Edgar Wideman une lecture qui s’oppose au cliché populaire de la propension chez les Noirs aux Etats-Unis à la paresse, donc au refus de travailler, et à la violence consubstantielle aux grandes poches urbaines frappées par le chômage de masse. Il tire ses exemple d’un corpus composé du Homewood Trilogy, A Glance Away, Philadelphia Fire, et Reuben, autour duquel il articule sa réflexion afin de démontrer que les Afro-Americains sont victimes d’un contexte historique et social de discrimination contre lequel ils doivent cependant lutter pour leur épanouissement. L’approche littéraire marxiste et le Critical Race Theory ont servi de cadre théorique à l’étude
Keywords: unemployment - violence - poverty - African; American – discrimination; chômage – violence – pauvreté –AfricainAméricain – discrimination